Spiritual Support In Chronic Renal Failure Patients With Hemodialysis : A Systematic Literature Review - Maisyaroh, Arista; Widianto, Eko Prasetya; Kurnianto, Syaifuddin; Rizky, Hilmi Miftahur (Universitas Airlangga, 2024)
Introduction: Chronic renal failure (CRF) is a terminal condition. For decades, hemodialysis has become a chosen treatment for CRF patients to keep alive. Nevertheless. anxiety associated with the disease remains a major concern among this particular population. Therefore, spiritual therapy is given reduce the level of anxiety. This literature review aims to explore the benefits of spiritual therapies: reading and listening to prayers, supportive education, and counseling. Methods: In this study the authors used the Literature Review method. Data collection methods with electronic databases are carried out through Spinger Link, PubMed, and ProQuest. Data were obtained from January 2022 to May 2022, included articles were full-text primary research, focused on spirituality support in CRF patients with Hemodialysis, within the publication period of 2017-2024. Exclusion criteria details are available in the full manuscript. To address the potential limitations introduced by language bias, only English and Indonesian-language publications were included. Instruments to assess the success of spiritual support in chronic renal failure patients with hemodialysis consist of the Daily Spiritual Experiences Questionnaire (DSES), HADS, CES-D: Epidemiologist Study Center Depression Scale, SWBS (Spirituality Well Being Scale) DUREL, Interview, RSC-brief, Questionnaire and Physical Symptom Distress Scale, PSQI Chinese version, Geriatric Depression Scale and Spiritual Well-Being Scale. Results: Ten (n= 10) articles were retrieved. Those described the benefits of spiritual therapies: reading and listening to prayers, supportive education and counseling. The level of anxiety among hemodialysis patients decrease after the treatments were given. The single and whole treatment can be applied daily, and no negatives of treatments were reported. Conclusions: Spiritual support positively reduce anxiety in patients with CRF with hemodialysis. Nurse is highly recommended to include spiritual education, counseling, listening to prayers, and reading prayers in anxiety associated with hemodialysis management in to nursing care plan. Further research examining the effect of spiritual treatment for patients in their early living with hemodialysis and those with long life span is necessary.